Implementasi Pembelajaran Al-Qur'an di SDIT Istiqamah Balikpapan Kota - Fedrika Intan Kumala Dewi; Siti Kamilah; suherman (At-Tarbiyah Jurnal Pendidikan,Kebudayaan dan Keislaman, 2025)
This study aims to understand how the implementation of Qur’an learning using the Ummi method takes place at SDIT Istiqamah in Balikpapan City, and to explore why the Ummi method is applied in Qur’an learning at SDIT Istiqamah. The background of this research stems from the transition of the Qur’an learning method from Tilawati to Ummi, due to the previous method being considered to lack clear standardization and evaluation. This study uses a qualitative approach with a case study design. Data collection techniques include observation, structured interviews, and documentation. The data analysis techniques used involve data collection, data reduction, data presentation, and drawing conclusions. The results show that the Ummi method is implemented in a structured manner according to the Ummi Foundation standards, with teachers acting as the main facilitators from apperception to evaluation. Supporting factors include the school management’s commitment, certified teachers, adequate learning facilities, and parental support. Inhibiting factors consist of poor student-teacher ratio, differences in textbook volumes within the same group, and lack of internal coordination. Overall, the Ummi method helps students read the Qur’an better; however, to achieve better results, improvements in management, workforce strengthening, and collaboration between the school and parents are needed.